Cytotoxic and Apoptotic Effect of Commercial Tinctures of Scutellaria baicalensis on Lung Cancer Cell Lines - Mbagwu IS,Ilodigwe EE.,Ajaghaku DL, Uzodinma SU, Osonwa UE (Journal of Applied Pharmaceutical Science, 2013)
The cytotoxic and apoptotic potentials of four commercial tinctures of S. baicalensis (SB1, SB2, SB3 and SB4) were investigated on three human lung cancer cells SK-MES-1, SK-LU-1 and A549. The number of cells that survived treatment with different concentrations of the tincture in 24, 48 and 72 hours was quantified by the colorimetric MTT assay. Acridine orange/ Propidium iodide dye exclusion assay was used to test for apoptosis in 24 and 48 hours at 200 μg/ml concentration of the tinctures. All the tinctures except SB4 showed a dose and time-dependent effect on the cancer cells. The minimum cytotoxic concentration of SB1, SB2, and SB3 sample tinctures on the SK-MES-1 and SK-LU-1 cells was approximately 100 μg/ml in 48 hours. 100 μg/ml of SB1 and SB2 tinctures have significant (p
Keywords: Apoptosis, Cancer, Scutellaria baicalensis.